Stakeholder Mapping Analysis Of First 1000 Days Of Life Program In Semarang - Dian Nursanti; Sutopo Patria Jati; M. Zen Rahfiludin (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
There is a gap between the implementation of the first 1000 days of life Program on the Implementation Guidelines in Semarang City, among others health workers are not well informed about the program, there is no specific structure in the implementation of first 1000 days of life program in Semarang City in accordance with the first 1000 days of life program Implementation Guidelines, and there has not been an integrated step from the Health Department related to the first 1000 days of life program, therefore it is necessary to analyze stakeholder mapping related to its role and function in supporting the 1000HPK program.This research is an observatioal research with qualitative method. Respondents in this study were representatives of stakeholders involved in the 1000HPK Program in Semarang City. In determining the respondents, the researcher uses purposive sampling to assess stakeholder perceptions on the level of influence of power, level of interest, and attitudes of each stakeholder linked to the role of each stakeholder and process indicator of the first 1000 days of life program.The modification group of the stakeholder classification model is as follows: Decision makers include: Regional People's Representative Assembly of Semarang City and BAPPEDA Semarang City, Provider: Health Office of Semarang City, IBI (Indonesian Midwives Association) Semarang City, IDI (Indonesian Doctors Association) Semarang City, Ministry of Religious Affairs Semarang, Education Office of Semarang City, and Academics. Client: PHC, Pregnant Women, Breastfeeding Mothers, Cadre (Dasawisma). Representative: FMM (Forum Masyarakat Madani), Business World, Print Media, Television Media.The results of identification of stakeholders of decision makers and client groups, all states support for the first 1000 days of life Program Process Indicators, but for the provider stakeholders there are groups in the